Radiation-Induced Hydrogel for Water Treatment - SK Nazmul Haque; Md Murshed Bhuyan; Jae-Ho Jeong (Gels, 2024)
Along with serving as drug delivery sensors and flexible devices, hydrogels are playing pioneering roles in water purification. Both chemical and radiation methods can produce hydrogels, with the latter method gaining preference for its pure adducts. The water treatment process entails the removal of heavy and toxic metals (above the threshold amount), dyes, and solid wastes from industrial effluents, seawater, and groundwater, as well as sterilization for microorganism destruction. This review analyzed the different types of hydrogels produced by applying various radiations for water treatment. Particularly, we examined the hydrogels created through the application of varying levels of gamma and electron beam radiation from the electron gun and Co-60 sources. Moreover, we discuss the optimized radiation doses, the compositions (monomers and polymers) of raw materials required for hydrogel preparation, and their performance in water purification. We present and predict the current state and future possibilities of radiation-induced hydrogels. We explain and compare the superiority of one radiation method over other radiation methods (UV-visible, X-ray, microwave, etc.) based on water treatment.